Edukasi tentang Pencegahan Stunting pada 1000 Hari Kehidupan Balita melalui Pemanfaatan Tanaman Herbal di Desa Kemetul - Pujiastuti, Anasthasia; Rissa Laila Vifta; Tina Mawardika (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2024)
Kemetul Village is one of the villages located in Susukan District, Semarang Regency. Based on the results of a survey from target partners, it is known that residents of Kemetul Village have never received information about stunting, causes and dangers. Target partners have never received education about the importance of preventing stunting during the 1000 days of a toddler's life and the use of herbal plants to improve toddler nutrition. This community service program was carried out using educational methods for housewives in Kemetul Village, Susukan District, Semarang Regency. The number of participants who took part in educational activities was 30 participants consisting of housewives and several elderly people. The percentage of participants' evaluation results before being given education fell into the category of less understanding at 56.6%, quite understanding 26.6%, good understanding 16.6% and very good 0%. Participants' understanding increased after being given education, namely being included in the very good category at 53.3%, good at 43.3%, fair at 3.3% and poor at 0%. Based on the participant understanding questionnaire, it was found that after being given education there was an increase in participants' understanding of stunting by 96.6%.   ABSTRAK                 Desa Kemetul merupakan salah satu Desa yang terletak di Kecamatan Susukan, Kabupaten Semarang. Berdasarkan hasil survey kepada mitra sasaran diketahui warga Desa Kemetul belum pernah mendapatkan informasi terkait stunting, penyebab dan bahayanya. Mitra sasaran belum pernah mendapatkan edukasi tentang pentingnya pencegahan stunting pada 1000 hari kehidupan Balita serta pemanfaatan tanaman herbal untuk meningkatkan gizi balita. Pelaksanaan kegiatan pengabdiaan kepada masyarakat ini dilakukan dengan metode edukasi pada ibu rumah tangga di Desa Kemetul, Kecamatan Susukan, Kabupaten Semarang. Jumlah peserta yang mengikuti kegiatan edukasi yaitu 30 peserta yang terdiri dari ibu rumah tangga dan beberapa lansia. Persentase hasil evaluasi peserta sebelum diberikan edukasi masuk dalam kategori kurang paham sebanyak 56,6%, cukup paham 26,6%, pemahaman yang baik 16,6% dan sangat baik 0%. Pemahaman peserta mengalami peningkatan setelah diberikan edukasi yaitu termasuk dalam kategori sangat baik sebesar 53,3%, baik 43,3%, cukup 3,3% dan kurang sebanyak 0%. Berdasarkan kuesioner pemahaman peserta diketahui bahwa setelah diberikan edukasi terdapat peningkatan pemahaman tentang penyakit stunting sebesar 96,6%.